ANALISIS STRUKTUR SLAB ON PILE STUDI KASUS JALAN TOL SEMARANG DEMAK SEKSI 2 - Santoso, Thomas Marcellino; Wahyudi, Muhammad Sigit; Muhrozi, Muhrozi; Atmanto, Indrastono Dwi (Teknika, 2022)
Slab on pile is one of the bridge structures used in the Semarang Demak Toll Road Project Section 2. The slab on pile structure consists of a slab, pile head, and piles. There are 2 (two) typical slab on pile bridges at this location, which are distinguished by the number and distance of the piles. 5 (five) piles in 1 (one) pile head with a spacing of 3.5 meters are used for piles with a freestanding of less than 6 meters. This pile configuration is located at STA 19 +658 to 19+793. Meanwhile, 6 (six) piles with a space of 2.8 m are used for piles with freestanding of more than 6 meters. This pile configuration is located at STA 19+800 to 19+894. At STA 19+674 there is an expansion joint that functions to accommodate all forms of movement that occur in the slab on pile structure. In addition, the span between the piles in the longitudinal direction is 7 meters. This slab on pile planning (SNI 1725:2016) "Loading for Bridges" and "Bridge Planning for Earthquake Loads" (SNI 2833:2016). Slab on pile planning is carried out with the help of SAP2000 software to determine the internal forces that occur in the slab on pile structure. The foundation system used in the modeling is a pile with spring support where the function of the spring support is to represent the nature of the soil. The result of this plan is to obtain a slab on pile structure design along with shop drawings.